2014
DOI: 10.1111/bjhp.12095
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant content validity: A quantitative methodology for assessing content of theory‐based measures, with illustrative applications

Abstract: The DCV method allowed quantitative assessment of each item and can therefore inform the content validity of the measures assessed. The methods can be applied to assess content validity before or after collecting data to select the appropriate items to measure theoretical constructs. Further, the data reported for each item in Appendix S1 can be used in item or measure selection. Statement of contribution What is already known on this subject? There are agreed methods of assessing and reporting construct valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 63 publications
2
96
0
11
Order By: Relevance
“…74,77 BCT × domain pairings that had no confidence rating from individual participants (i.e. BCT was not allocated to that domain by that participant) were scored zero and entered into the mean score for that pairing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74,77 BCT × domain pairings that had no confidence rating from individual participants (i.e. BCT was not allocated to that domain by that participant) were scored zero and entered into the mean score for that pairing.…”
Section: Discussionmentioning
confidence: 99%
“…There was no overlap in participants between the 'bottom-up' and 'top-down' sort tasks. The sample size for the closed-sort task was based on estimates given for content-validation exercises, with 2-24 participants being shown to be sufficient [74][75][76][77] and more than five participants reducing the influence of rater outliers. 78 …”
Section: Behaviour Change Technique Taxonomy Version 1 With Hierarchimentioning
confidence: 99%
“…We already have enormous 'variability 'of theories and constructs explaining behaviour and behaviour change and would gain by 'eliminating gaps in theories, reducing redundancy, and increasing parsimony' (Hagger, 2009, p.190). There are at least 83 theories of behaviour change and over 1700 constructs (Michie, West, Campbell, Brown Gainforth, 2015) but how many are distinct (Schüz, Sniehotta, Mallach, Wiedemann & Schwarzer, (2007) and how many can be operationalised separately (Johnston, Dixon, Hart, Glidewell, Schröder, & Pollard, 2014)? Creative shifts may lose what was already 'known'; for example, the shift to cognitive models appears to have lost the evidence associated with behavioural models and surprise is expressed that the removal of financial rewards leads to extinction of a learned health-related behaviour, a phenomenon easily explicable by early twentieth century science (Johnston, 2015).…”
Section: Scientific Advancementioning
confidence: 99%
“…If there is poor content validity and the measures used in a study do not discriminate among constructs, any identified relationships may be of questionable value [30].…”
Section: Measurement Of Impairment Activity Limitation and Participamentioning
confidence: 99%
“…Items from the RAND-36 Item Short Form Health Survey [43] 24,25,26,28,30). All these impairment outcomes have been shown to measure impairment with discriminant validity [44].…”
Section: Impairmentsmentioning
confidence: 99%